Molecular detection of zoonotic Spirometra (Cestoda: Diphyllobothriidae) in Javan-spitting cobra (Naja sputatrix) snakes in Indonesia - ADITYA YUDHANA; ANJANI MARISA KARTIKASARI; RYANKA EDILA; RATIH NOVITA PRAJA; JONATHAN MARK HAMONANGAN; APRIL HARI WARDHANA; MUFASIRIN MUFASIRIN; SETIAWAN KOESDARTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yudhana A, Kartikasari AM, Edila R, Praja RN, Hamonangan JM, Wardhana AH, Mufasirin, Koesdarto S. 2024. Molecular detection of zoonotic Spirometra (Cestoda: Diphyllobothriidae) in Javan-spitting cobra (Naja sputatrix) snakes in Indonesia. Biodiversitas 25: 4853-4859. Sparganosis, a neglected disease caused by the larvae of Spirometra tapeworms, is considered a serious threat to public health worldwide. However, data on snake prevalence or molecular study of sparganosis in snakes still needs to be improved. In this study, we aim to investigate the prevalence of plerocercoids (spargana) infection in wild-caught Javan-spitting cobra (Naja sputatrix) snakes in Banyuwangi, East Java Province, Indonesia, using morphological and molecular identification methods. A total of 70 Javan-spitting cobra snakes were purchased from local sellers in Banyuwangi, Indonesia. Morphological identification was conducted on a plerocercoids collected from various predilection sites. Moreover, molecular identification was done by polymerase chain the Polymerase Chain reaction (PCR) method and analyzed using the mitochondrial cytochrome c oxidase subunit 1 (cox1) gene. Plerocercoids were identified in 70 snakes, with the prevalence rate recorded at 60%. A total of 231 plerocercoids were collected and divided into 184 (79.65%) in muscular and 47 (20.34%) in subcutaneous tissues. The plerocercoids were macroscopically identified as thin, flat, and white colored with ribbon-like structure and were 2-14 cm long and 2-8 mm wide. Microscopic examination of plerocercoids using the carmine staining method revealed a mouth-like shape anterior side. Furthermore, PCR analysis results reveal that 5 plerocercoid specimens were identified as Spirometra, and each sample shows positive bands at 467 bp. To our knowledge, this study is the first report of Spirometra in species of Indonesian endemic snake primarily on Java Island. These findings constitute a serious potential risk of human sparganosis transmission in Indonesia because wild-caught Javan-spitting cobra snakes are locally used as human food.